PERSEPSI TERHADAP APLIKASI TIKTOK ATAS DASAR GENDER DAN DAMPAK YANG DITIMBULKAN PADA KEGIATAN PROMOSI - Sutrisno Sutrisno (Jurnal Bina Manajemen, 2022)
Tiktok is included in digital content that is currently very popular with the general public, especially millennials. This study was conducted to seek support for empirical data regarding the difference in the mean scores of the group who think TikTok has a positive impact and another group who think that TikTok has a negative impact. In addition, a hypothesis was also developed to test whether there was a difference in the duration of time on the use of the TikTok applicationbetween male and female genders. Data was collected using the Convenience Sampling sampling technique using communication techniques through conducting a survey using Google Form. Tests were carried out using tests for both independent populations at the level of significance of 5%. The results found that the average impact response of people who thought there was a positive impact was not significantly different from that of people who had a negative opinion of TikTok. Besides, the length or short duration of using TikTok is not affected by the gender of the user.